Hepatic Steatosis and Cirrhosis in Bariatric Surgery Patients: Intraoperative Decision-Making and Postoperative Outcomes - Abdussalam Hounki; Karima Alfitory (AlQalam Journal of Medical and Applied Sciences, 2026)
The global increase in morbid obesity has been accompanied by a rising prevalence of non-alcoholic fatty liver disease (NAFLD), which may progress silently to non-alcoholic steatohepatitis, advanced fibrosis, and cirrhosis. Bariatric surgery is the most effective treatment for obesity-related metabolic disease; however, malabsorptive procedures such as Roux-en-Y gastric bypass may confer increased perioperative risk in patients with impaired hepatic reserve. To report a series of bariatric surgery candidates in whom advanced fatty liver disease or cirrhosis was unexpectedly identified intraoperatively and to highlight the subsequent surgical decision-making process favoring safer operative alternatives. This case series includes three female patients aged 43 to 52 years with body mass indices ranging from 38 to 44 kg/m² who were scheduled for Roux-en-Y gastric bypass. Preoperative laboratory, radiological, and endoscopic evaluations were normal or demonstrated only minimal abnormalities. In all cases, intraoperative inspection revealed macroscopic features suggestive of advanced fatty liver disease or cirrhosis, prompting immediate intraoperative liver biopsy for histopathological confirmation. Histopathological analysis confirmed advanced hepatic pathology in all three patients. Consequently, the planned Roux-en-Y gastric bypass procedures were abandoned and converted to sleeve gastrectomy to reduce operative stress, avoid malabsorption, and minimize the risk of hepatic decompensation. Postoperative recovery was uneventful in all cases, with satisfactory early weight loss and no evidence of short-term hepatic deterioration. Sleeve gastrectomy represents a safer and effective bariatric option for patients with incidentally discovered cirrhosis or advanced fatty liver disease. This case series underscores the limitations of standard preoperative screening and highlights the critical importance of intraoperative liver assessment and biopsy in guiding individualized surgical decision-making.